Organizational Consensus Regarding the Relative Importance of Research Output Indicators. - Chan, James L. (The Accounting Review, 1978)
Abstract A knowledge-recognition social exchange model is proposed in this article to conceptualize academic research as a sequential interdependent process. The importance of peer evaluation and feedback to the researcher is emphasized. University goals and their inter-relationships with resource allocation decisions are discussed. The paper reports the results of a survey to ascertain organizational consensus regarding the relative importance of research output indicators in the evaluation of the effectiveness of academic engineering departments' research programs. There is a general consensus among faculty members and between faculty and administrators to attribute the highest importance to papers published in scholarly journals. The regard for the importance of research proposals, however, is not widely shared. The study recommends published papers, invited papers and dissertations as output indicators to be measured by a university's system.